(untitled) (The Peerian Journal, 2022)
This paper demonstrates the results of an observation in teaching, confirming the productiveness of teaching English language to medical students by using professionallyoriented Project-Based Learning. The article proved that during its accomplishment and practical training, students have been achieved self-supporting work experiences, have improved their creative and critical thinking, have developed intercultural awareness and learn skills on how to work in a team, as well as inspiration to learn English language